WATER CONSUMPTION MODEL FOR THREE STAR HOTELS IN MAJORCA - Escalera Izquierdo, Gregorio; Pérez Zabaleta, Amelia; Vizcaíno Pérez, Luis (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2013)
The purpose of this article is to develop a method to obtain a mathematical model for monthly water consumption versus occupation, from historical data from hotels, using linear regressions, validated by the square of the Pearson correlation coefficient. Based on data of Majorca hotels with common studied characteristics, current consumption is modeled for each hotel and the group of hotels. Minimum values by intervals of occupation can be obtained from the corresponding optimal models. It is concluded that the methodology displayed for selection of data and hotels, allowed to reach values of the square of the correlation coefficient, higher than 0.89 in the optimal models of the hotels studied.